NSCT‐based fusion method for forward‐looking sonar image mosaic. Issue 10 (1st October 2017) - Zhang, Jian; Sohel, Ferdous; Bennamoun, Mohammed; Bian, Hongyu; An, Senjian
Abstract : To generate a seamless mosaic of a forward‐looking sonar (FLS) video sequence, this study proposes a novel fusion method for FLS image mosaic, which includes two main steps from coarse to fine. In the coarse fusion step, the source images are first decomposed into multi‐scale sub‐bands using the non‐subsampled contourlet transform (NSCT), then the sub‐bands of the source images are merged, based on the Gabor energy and the local contrast for low and high frequency sub‐bands, respectively, to generate the fused sub‐bands which are used to produce the fused image by inverse NSCT. In the fine fusion step, a decision map is used to choose the pixels of the fine fused image from the coarsely fused image or one of the source images. This decision map is first constructed by measuring the similarity of the coarsely fused image to the source images, and then processed by a morphological post‐processing technique to ensure its continuity and smoothness. Extensive experiments on FLS image fusion and mosaic have been conducted to demonstrate the effectiveness and the superiority of the proposed technique using both a subjective evaluation and objective metrics.